Organization of Accounting, Audit and Analysis in the Effective Use of Labour Force in the Enterprise - Arsentieva Olena, Ivchuk Yuliia, Kotova Liubov, Reznik Nadiia (International Journal of Advanced Science and Technology, 2020)
The article explores the concept of the enterprise labour force, their characteristics. Organization of accounting and audit of the labour force. The main indicators and the process of analyzing the efficiency of the enterprise’s labour force are determined.